Fear of COVID-19, healthy eating behaviors, and health-related behavior changes as associated with anxiety and depression among medical students: An online survey - Nguyen, Minh H.; Do, Tinh X.; Nguyen, Tham T.; Pham, Minh D.; Pham, Thu T. M.; Pham, Khue M.; Kim, Giang B.; Do, Binh N.; Nguyen, Hiep T.; Nguyen, Ngoc-Minh; Dam, Hoa T. B.; Nguyen, Yen H.; et al. (Frontiers in Nutrition, 2022)
Background Medical students’ health and well-being are highly concerned during the COVID-19 pandemic. This study examined the impacts of fear of COVID-19 (FCoV-19S), healthy eating behavior, and health-related behavior changes on anxiety and depression. Methods We conducted an online survey at 8 medical universities in Vietnam from 7th April to 31st May 2020. Data of 5765 medical students were collected regarding demographic characteristics, FCoV-19S, health-related behaviors, healthy eating score (HES), anxiety, and depression. Logistic regression analyses were used to explore associations. Results A lower likelihood of anxiety and depression were found in students with a higher HES score (OR= 0.98; 95%CI= 0.96, 0.99; p= 0.042; OR= 0.98; 95%CI= 0.96, 0.99; p= 0.021), and in those unchanged or more physical activities during the pandemic (OR= 0.54; 95%CI= 0.44, 0.66; p<0.001; OR= 0.44; 95%CI= 0.37, 0.52; p<0.001) as compared to those with none/less physical activity, respectively. A higher likelihood of anxiety and depression were reported in students with a higher FCoV-19S score (OR= 1.09; 95%CI= 1.07, 1.12; p<0.001; OR= 1.06; 95%CI= 1.04, 1.08; p<0.001), and those smoked unchanged/more during the pandemic (OR= 6.67; 95%CI= 4.71, 9.43; p<0.001; OR= 6.77; 95%CI= 4.89, 9.38; p<0.001) as compared to those stopped/less smoke, respectively. In addition, male students had a lower likelihood of anxiety (OR= 0.79; 95%CI= 0.65, 0.98; p= 0.029) compared to female ones. Conclusions During the pandemic, FCoV-19S and cigarette smoking had adverse impacts on medical students’ psychological health. Conversely, staying physically active and having healthy eating behaviors could potentially prevent medical students from anxiety and depressive symptoms.